Tatort Gesundheitsmarkt - Rechtswirklichkeit - Strafwürdigkeit - Prävention - Duttge, Gunnar (Universitätsverlag Göttingen, 2011)
Reports on medical billing frauds, "premiums" of hospitals (for the referral of a patient) as well as the "medical marketing" arouse increasing attention in times of dwindling financial resources within the socially insured healthcare system and the worry for spreading "rationing". Out of consideration for the partly remarkably high financial damages the call for a harsh punishment suggests itself, but the criminal law is always late and, above all, isn't capable of compensating the intangible loss of trust. Therefore, the search for instruments of an effective prevention of corruption deserves far more notice, but consequently the question of the real criminal events and of the possible "adjusting screws" for preventive interventions as well. The articles in this volume, which come from the recent (organized on 8 July 2011) annual conference of the Institute of Criminal Law and Justice in Göttingen, present the latest findings available so far. They may provide the interested public with an insight, that is respectably and not clouded by the drive of mass-media scandalisation, into the extent and appearances of corrupt behaviour in the healthcare system and may give the experts suggestions for productive further discussions and innovative problem solvings.